Development of E-Module Based on HOTS Questions on Distance Material for High School Students - Tobing, Hendrik Efendi Lumban; Somakim; Susanti, Ely (Mathematics Education Journal, 2022)
This research aimed to develop a valid and practical electronic module that potentially affected the HOTS of grade 12 students during distance learning in Xaverius 1 High School, Palembang. This study employed the Alessi Trollip model orienting towards multimedia products consisting of three stages: planning, designing, and developing. The data collection techniques were validation sheet instruments, questionnaires, and tests. Meanwhile, the data analysis method were validation sheets and questionnaires through average scores and comments and test sheets through student work. The success criteria of this research were to obtain valid and practical geometry distance teaching materials with HOTS by considering experts’ and clients’ reviews. The expert validity revealed a score of 4.72 and was considered very valid. The questions’ score was 55.5% and was revised. Meanwhile, the questionnaire was categorized practical with a score of 79.3. The e-module potentially influenced HOTS exercises with an average score of 83.5 or very good. This research concludes that the developed e-module has valid and practical characteristics and can influence the HOTS thinking abilities to create and analyze. Thus, the module significantly supports the needs of teaching materials and increases the students’ HOTS.DOI: https://doi.org/10.22342/jpm.16.1.14694.1-14